(untitled) - Brinkley, Captain F. (Boston, 1902)
This book introduce about manners and customs of the Tokugawa era, the Tokugawa court. Criminal procedure and the criminal classes in Tokugawa times. Personal liberty, justice, slavery, and checks on vicw, philosophy, education, customs, and costumes. Meiji, or the era of "Englightened government".
Keywords: Nhật Bản,Japan; Lịch sử,History